2005
DOI: 10.1186/1471-2431-5-32
|View full text |Cite
|
Sign up to set email alerts
|

Parents' psychological adjustment in families of children with Spina Bifida: a meta-analysis

Abstract: Background: Spina Bifida (SB) is the second most common birth defect worldwide. Since the chances of survival in children with severe SB-forms have increased, medical care has shifted its emphasis from life-saving interventions to fostering the quality of life for these children and their families. Little is known, however, about the impact of SB on family adjustment. Reviewers have struggled to synthesize the few contradictory studies available. In this systematic review a new attempt was made to summarize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
93
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 54 publications
4
93
0
5
Order By: Relevance
“…3 Sources of stress among these parents include sudden impact life events (for example, at the time of diagnosis and surgery) as well as the repetitive, daily problems (for example, ambulation and incontinence problems) that contribute to chronic impact. 4 These parents need to cope with large amounts of technical medical information, adjust to the new demands on their own daily routines and make important decisions about the medical, social and schooling needs of their children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Sources of stress among these parents include sudden impact life events (for example, at the time of diagnosis and surgery) as well as the repetitive, daily problems (for example, ambulation and incontinence problems) that contribute to chronic impact. 4 These parents need to cope with large amounts of technical medical information, adjust to the new demands on their own daily routines and make important decisions about the medical, social and schooling needs of their children.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] A meta-analysis has shown that spina bifida has a negative medium-large effect on parental psychological adjustment, with the most important effect on parent-child relationship. 3 Mothers have been shown to be more at risk than fathers, probably because they often are the main caregivers and consequently are more exposed to illness-related situations. 4,9 Few studies have been done among Asian families having children with chronic disorders wherein the social and cultural outlook, as well as medical services, differs.…”
Section: Introductionmentioning
confidence: 99%
“…Parents of youth with disabilities experience more stress than parents of able-bodied youth. 1,2 Similarly, caregivers of adults with SCI report experiencing a low quality of life, 3,4 burden 5 and psychological distress. 6 Factors associated with poorer caregiver outcomes include less education, 6 not having a partner, 2 being female, 5,6 having a child of older age 2 and caring for a person/child with behavioral/ emotional problems.…”
Section: Introductionmentioning
confidence: 99%
“…6 Factors associated with poorer caregiver outcomes include less education, 6 not having a partner, 2 being female, 5,6 having a child of older age 2 and caring for a person/child with behavioral/ emotional problems. 2 The impact of injury severity and injury duration is unclear, as some researchers 5 have found that these factors predict poor caregiver outcomes, whereas others 6 have found no such relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Children with SB have a range of disabilities, depending on where in the spinal column formation the defect is located and whether it is closed or open (7). Children with SB do not present simply with flaccid paraplegia below their anatomic lesion.…”
Section: Introductionmentioning
confidence: 99%